Comprehensive recovery of metals from cyanidation tailing. (January 2015) - Lv, C.C.; Ding, J.; Qian, P.; Li, Q.C.; Ye, S.F.; Chen, Y.F.
Highlights: Cyanidation tailing can be treated by sodium hypochlorite to recover low grade metals. Sodium hypochlorite played a significant role of oxidizing agent and pH regulator. The total cyanide in the tailing pulp decreased with the increase of sodium hypochlorite. Qualified Cu concentrate and Zn concentrate can be acquired from the cyanidation tailing. We offer an comprehensive model to recover valuable minerals from tailing. Abstract: Cyanidation tailing is the residue produced in gold plants which use cyanidation to extract gold. It can be used as a secondary resource to recover residual metals that are of great economic value. The cyanidation tailing investigated in this paper was obtained from Shandong Province, China. It contained valuable metals such as chalcopyrite, galena, sphalerite and pyrite. In this study, alkaline sodium hypochlorite was used as a regulator in the pretreatment stage. It was proved that the sodium hypochlorite played two roles in the flotation pulp: oxidant and pH regulator. On one hand, sodium hypochlorite oxidized cyanide to cyanate, eliminating the negative effect of residual cyanide towards the environment. On the other hand, with the pH of flotation pulp exceeding 10, sphalerite and pyrite were depressed enormously, which was beneficial to the recovery of chalcopyrite and galena. With the Cu–Pb bulk flotation flowsheet, the cyanidation tailing was processed to obtain qualified Cu concentrate with grade of 13.17% and recovery of 70.00% compared with the original Cu grade of 0.21%. The Cu–Pb tailing was processed to obtain qualified Zn concentrate with grade of 34.72% and recovery of 69.58% compared with the original Zn grade of 0.33%, constituting the comprehensive recovery routing for the cyanidation tailing.